Organizational Communication Model In Maintaining The Work Ethic Of Employees Of The Regional Revenue Agency Office Of Southeast Sulawesi Province - La Ode Mahbub; Jamallulail Jamallulail (LPPM Universitas PGRI Sumatera Barat, 2024)
To maintain the Work Ethic of Employees, the communication model is one of the important things that need to be understood and applied appropriately to an organization or government agency. However, sometimes the communication model is not sufficiently understood and appropriate in its application so it has implications for mass communication in all members of the organization, both subordinates and superiors and so on. This research aims to analyze the application of the organizational communication model at the Regional Revenue Agency Office of Southeast Sulawesi Province and to analyze how to maintain employee work ethic related to the communication model. To analyze the communication model, Robbins (2013) uses the theory of the Chain Model, Wheel Model, Circle Model, Free Network Model (all channels), and the